Expression of major haemoglobin haplotypes in the first twenty-four months of life suggests a gradual decline of normal haemoglobin A among infants of African descent.: Haemoglobin haplotypes expression in infancy - Jeremiah, Zaccheaus; Neenwi, Edna Mueka (Medicinska istraživanja, 2025)
Introduction: Haemoglobin is the principal protein in red blood cells and is responsible for delivering oxygen from the lungs to other body parts. Understanding the haemoglobin type profile of infants and the patterns of expression in the first twenty-four months of life is a significant area of research that can provide crucial insights into infant health and development. Materials and Methods: The study population consisted of 147 infants (male and female) aged 9 to 24 months. Participants were recruited from the paediatric and sickle cell clinics and the medical laboratory department of Rivers State University Teaching Hospital (RSUTH) in Port Harcourt, Nigeria. The haemoglobin type was determined using high-performance liquid chromatography (HPLC) (D-10, Bio-Rad). Results: The mean values of the haemoglobin types were: Hb A (66.31 ± 1.46%), Hb F (14.67 ± 1.14%), Hb S (14.52 ± 1.85%) (p<0.0001) and A2 (4.47 ± 0.71%) (p>0.05). Haemoglobin A expression was 65% at nine months, 79% at 12.5 months, 46% at 22 and 60% at 24 months. HbF expression was 21% at nine months, 10% at 12 months, 24% at 15.5 months, 0.25% at 21 months, and 12% at 24 months. HbS was 0.8% at nine months and 0% at 16 months. 50% at 22 months and lastly 22% at 24 months. The HbA2 was 0.5% at nine months and 12% at 11 months. 0% at 21 months and lastly 0.2% at 24 months. HbA, HbF, and HbA2 were negatively correlated with age, while HbS was positively correlated with age. Conclusion: The pattern of expression of the four haemoglobin types in this study was age-dependent. Sex was not found to influence the expression of haemoglobin types in infants. There is a gradual reduction in the expression of normal haemoglobin A and a gradual increase in abnormal haemoglobin S among infants of African descent.